(untitled) (Islas, 2020)
Considero relevante incursionar en la genealogía del concepto de sociedad civil para describir y analizar el fenómeno en nuestros días. Existen dos razones que justifican esta búsqueda de los orígenes del concepto de sociedad civil. La primera de ellas remite a la comprensión de la acción política que llevan a cabo las organizaciones de la sociedad civil en la esfera pública en diferentes contextos históricos; y la segunda deriva de la necesidad de aclarar las diferencias entre la visión clásica y la perspectiva contemporánea de la sociedad civil. I consider relevant to venture into the genealogy of the concept of civil society to describe and analyze this phenomenon in our day. There are two reasons that justify this search for the origins of the concept of civil society. The first one refers to the understanding of political action carried out by civil society organizations in the public sphere in different historical contexts; and the second derives from the need to clarify the differences between the classical vision and the contemporary perspective of civil society.